Environmental, Social, and Governance and Firm Value: The Mediating Role of Financial Performance in Indonesia - Agung Dinarjito; Puji Wibowo (Penerbit Goodwood, 2026)
Purpose: This study investigates the impact of Environmental, Social, and Governance (ESG) performance on corporate value, with financial performance acting as an intervening mechanism, in non-financial firms listed on the Indonesian Stock Exchange. Research Methodology: This study employs a quantitative research design using panel data from 30 non-financial firms over the period 2020–2023. ESG data are sourced from Bloomberg, while financial data are obtained from firms' annual reports. The sample is selected using purposive sampling. Data are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), which is suitable for prediction-oriented analysis and non-normal data distribution. Results: The findings reveal that aggregate ESG performance does not have a direct effect on corporate value. However, ESG performance significantly and positively influences financial performance, which in turn has a positive effect on corporate value. Conclusions: This study highlights that ESG performance enhances corporate value indirectly through financial performance, emphasizing the critical role of financial outcomes as a transmission channel of sustainability practices. Limitations: The study is limited by its focus on non-financial firms within a specific emerging market context and a relatively small sample size, which may restrict the generalizability of the findings. Contributions: This research extends the ESG literature by providing empirical evidence on the mediating role of financial performance in emerging markets. It offers practical implications for corporate managers to strategically integrate ESG initiatives with financial objectives and informs investors and policymakers about the indirect value relevance of ESG performance.